Identification and quantification of anthocyanins in transgenic purple tomato - Su, Xiaoyu; Xu, Jianteng; Rhodes, Davina; Shen, Yanting; Song, Weixing; Katz, Benjamin; Tomich, John; Wang, Weiqun (My University, 2016)
Anthocyanins are natural pigments derived from the phenylpropanoid pathway. Most tomatoes produce little anthocyanins, but the transgenic purple tomato biosynthesizes a high level of anthocyanins due to expression of two transcription factors (Del and Ros1). This study was to identify and quantify anthocyanins in this transgenic tomato line. Seven anthocyanins, including two new anthocyanins [malvidin-3-(p-coumaroyl)-rutinoside-5-glucoside and malvidin-3-(feruloyl)-rutinoside-5-glucoside], were identified by LC-MS/MS. Petunidin-3-(trans-coumaroyl)-rutinoside-5-glucoside and delphinidin-3-(trans-coumaroyl)-rutinoside-5-glucoside were the most abundant anthocyanins, making up 86% of the total anthocyanins. Compared to undetectable anthocyanins in the wild type, the contents of anthocyanins in the whole fruit, peel, and flesh of the Del/Ros1-transgenic tomato were 5.2 ± 0.5, 5.1 ± 0.5, and 5.8 ± 0.3 g/kg dry matter, respectively. Anthocyanins were undetectable in the seeds of both wide-type and transgenic tomato lines. Such novel and high levels of anthocyanins obtained in this transgenic tomato may provide unique functional products with potential health benefits.
Citation: Su, X., Xu, J., Rhodes, D., Shen, Y., Song, W., Katz, B., … Wang, W. (2016). Identification and quantification of anthocyanins in transgenic purple tomato. Food Chemistry, 202, 184–188. https://doi.org/10.1016/j.foodchem.2016.01.128
Keywords: Anthocyanins; Transgenic Tomatoes; Delila; Rosea1